Evaluación de la Efectividad de Manejo del área marino costeras Refugio de Vida Silvestre Isla Santa Clara - Cruz Cuenca, Melanny Jhoanna (2018)
Abstract:The Management Effectiveness Assessment (EEM) of the Santa Clara Island Wildlife Refuge (RVSISC) has been generated to provide strategic information on the current state and to establish the degree of compliance with conservation objectives and targets, mainly by updating the baseline of the site, compiling and reviewing all existing information from the Refuge, followed consecutively the determination that was taken as Hockings' frame of reference and methodology of the METT effectiveness evaluation, which was adapted specifically for Ramsar sites called RMETT for its acronym in English. The "Santa Clara Island" Wildlife Shelter management effectiveness assessment scored 1.7 and a percentage of 54%, equivalent to a satisfactory management. Finally, with the results obtained, a proposal was made for strengthening the management and scope of the Ramsar Site objectives, especially in Budget, Equipment and Infrastructure, Research, infrastructure for visitors and quotas, which were the least qualified, which they need to strengthen.